JOŽE ŽOHAR, A MIGRANT POET FROM AUSTRALIA AND HIS NEW COLLECTION OF VERSE OBIRANJE LIMON (2004) - Igor Maver (Dve Domovini, 2006)
Jože Žohar migrated »down under« to Australia in 1968 and struggles to pacify inside him the two homelands, Slovenia and Australia. In his three published collections of verse in the Slovene language (1990, 1995, 2004) the poet remains torn between the two countries, between Eros and Thanatos, between a unique erotic experiencing of the homeland and the wish for physical and spiritual ending and closeness of death, which brings deliverance. The article contextualizes his recently published book of verse Obiranje limon (2004) within recent theories of diasporic writing.